The island of sea women eaudiobook A novel. - See, Lisa (Simon & Schuster Audio, 2019)
THE NEW YORK TIMES BESTSELLER "A mesmerizing new historical novel" ( O, The Oprah Magazine ) from Lisa See, the bestselling author of The Tea Girl of Hummingbird Lane , about female friendship and devastating family secrets on a small Korean island. Mi-ja and Young-sook, two girls living on the Korean island of Jeju, are best friends who come from very different backgrounds. When they are old enough, they begin working in the sea with their village's all-female diving collective, led by Young-sook's mother. As the girls take up their positions as baby divers, they know they are beginning a life of excitement and responsibility—but also danger. Despite their love for each other, Mi-ja and Young-sook find it impossible to ignore their differences. The Island of Sea Women takes place over many decades, beginning during a period of Japanese colonialism in the 1930s and 1940s, followed by World War II, the Korean War, through the era of cell phones and wet suits for the women divers. Throughout this time, the residents of Jeju find themselves caught between warring empires. Mi-ja is the daughter of a Japanese collaborator. Young-sook was born into a long line of haenyeo and will inherit her mother's position leading the divers in their village. Little do the two friends know that forces outside their control will push their friendship to the breaking point. "This vivid...thoughtful and empathetic" novel ( The New York Times Book Review ) illuminates a world turned upside down, one where the women are in charge and the men take care of the children. "A wonderful ode to a truly singular group of women" ( Publishers Weekly ), The Island of Sea Women is a "beautiful story...about the endurance of friendship when it's pushed to its limits, and you...will love it" ( Cosmopolitan ).